A Rare Cause of Pneumomediastinum, Pneumothorax and Subcutaneous Emphysema After Performing Puncture-Dilation Tracheostomy - E. V. Kelekhsaeva; T. P. Suchilnikova; K. A. Popugaev; A. V. Bondarenko; Kh. V. Burnatsev; I. M. Valiev; K. V. Vetrova; N. M. Kruglyakov; A. K. Semenko; R. V. Tsakoev; O. O. Tsarakov; F. F. Khamitov; et al. (Неотложная медицинская помощь, 2025)
Tracheostomy is the most frequently performed operation in the intensive care unit. According to some data, the frequency of performance fluctuates within 0.1–0.5 cases per 1000 patients on artificial ventilation. In recent years, dilation techniques for applying a tracheostomy cannula have been actively developed due to their low trauma , the ability to perform the operation at the patient’s bedside, and rapid healing of the tracheostomy wound. Today, the “gold standard” of tracheostomy is puncture-dilation tracheostomy under fiberoptic bronchoscopic guidance.This method has its drawbacks, which is confirmed by a large number of complications. Thus, one of the complications of tracheostomy that is difficult to correct is the “gas” syndrome, which includes pneumomediastinum, subcutaneous emphysema and pneumothorax. These complications are considered to be a consequence of damage to the posterior wall of the trachea. Our clinical example demonstrates another mechanism for the development of the above complications.We present a clinical example of the development of subcutaneous emphysema, pneumomediastinum and pneumothorax without damage to the posterior wall of the trachea.